Electrochemical Studies of Betti Base and Its Copper(II) Complex by Cyclic and Elimination Voltammetry - Shardul Bhatt; Bhavna Trivedi (International Journal of Electrochemistry)
The electrochemical behavior of Betti base 1-(α-amino benzyl)-2-naphthol (BB) and its copper(II) complex by cyclic and elimination voltammetry (EVLS) is reported in the present study. The cyclic voltammetric studies carried out at a glassy carbon working electrode, Ag/Ag+ reference electrode (0.01 M AgNO3 in acetonitrile) in DCM at 100 mV/sec, 200 mV/sec, and 400 mV/sec scan rates indicated a preceding chemical oxidation of the adsorbed BB species to form an iminium ion followed by formation of a carbanion via two-step quasireversible reduction. The suggested reaction mechanism has been supported by the elimination voltammetry. The CV and EVLS studies revealed Cu(II)BB complex to undergo a chemical or a surface reaction before electron transfer from the electrode at −0.49 V to form Cu(I)BB species. The oxidation of Cu(I)BB species has been observed to be CV silent.